1989
DOI: 10.1136/emj.6.2.90
|View full text |Cite
|
Sign up to set email alerts
|

A review of trauma deaths in an accident and emergency department.

Abstract: SUMMARYThere were 56 deaths following trauma in the adult Accident and Emergency Department of the University Hospital, Nottingham, over a 5-year period from 1983 to 1987. Forty-six of these deaths followed road-traffic accidents.The trauma deaths made up 16% of all adult deaths and 0-13 per thousand new attenders. We found evidence of inappropriate management in four cases, all relating to inadequate volume replacement. In two patients, the degree of hypovolaemia was not appreciated and in the other two, volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 7 publications
3
4
0
Order By: Relevance
“…Many studies have also reported non-trauma emergencies as the leading cause of death in the AEU [16,17,19,20,24] with stroke and other cardiovascular diseases being the most common among the non-trauma causes [2,14,16,18,[20][21][22], [25]. In general, most previous studies agree that the death rate from trauma is higher in males than in females [8,[26][27][28][29]. In this study, the male-to-female death ratio from trauma was 7.4:1.…”
Section: Discussionsupporting
confidence: 60%
“…Many studies have also reported non-trauma emergencies as the leading cause of death in the AEU [16,17,19,20,24] with stroke and other cardiovascular diseases being the most common among the non-trauma causes [2,14,16,18,[20][21][22], [25]. In general, most previous studies agree that the death rate from trauma is higher in males than in females [8,[26][27][28][29]. In this study, the male-to-female death ratio from trauma was 7.4:1.…”
Section: Discussionsupporting
confidence: 60%
“…We identified 103 terms used to identify or describe QIs in our review. Although the field of quality improvement is fundamentally a process of change Peer review of trauma deaths to evaluate quality of care and determine whether the death was potentially preventable 19 Case series 13,19,34,39,50,69,76,79,85,87,99,115,[119][120][121]124,188,189,200 ; 18 cohort studies 10,18,37,49,62,86,109,113,122,140,145,149,151,178,187,194,196,207 ; 3 before-and-after case series 51,118,166 ; 2 nonrandomized controlled trials 16,205 ; and 1 cross-sectional study 17 Hospital mortality a 17 Cohort studies 7,43,49,52,63,…”
Section: Commentmentioning
confidence: 99%
“…The initial resuscitation of trauma patients is a period of time critical to patient outcome, with a well-described potential for error reduction [7][8][9][10]. Opportunities for quality improvement have been identified during airway management, fluid resuscitation, and diagnosis of life-threatening injuries [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%